An inclusive analysis of determinants of international migration. The case of European rich and poor countries - Mihi-Ramírez, Antonio; Kumpikaitė-Valiūnienė, Vilmantė; Cuenca-García, Eduardo (Technological and Economic Development of Economy, 2017)
This work aims to integrate defragmented migration perspectives in order to better understand and explain reasons of contemporaneous migration. Accordingly, international migration flows are explained with various socio-economic determinants which address different sources of migration, reinforced by the best-known theories and conceptual frameworks. A panel data analysis is performed at the level of rich and poor countries of the European Union to measure migration flows from the year 2000 until 2013. The results provide evidence indicating that there are some structural similarities and discrepancies between European rich and poor countries. These similarities (or discrepancies) make them responding similarly to certain economic conditions and changes. Thus, the association of earnings, inequalities (measured by the Gini Index) and poverty line could be positive or negative depending on wealth level of countries. Moreover, unemployment is a supply-push factor, but its importance is much higher in rich countries, diminishing in poorer countries. Economic freedom has a very strong positive effect on migration for all countries, but its relevance turned out to be the highest in the group of the poorest countries. Also, the association between Foreign Direct Investment and migration is negative, but it is more significant in the case of poorer countries.